Measuring the Impact of Operational Performance on Market Value in Private Iraqi Commercial Banks Using a Panel Data Model - Muhammad, Ali Hussein; Hamdan, Ahmed Abdulzahra (Research Parks Publishers, 2024)
The research aims to assess the impact of performance and on the added market value of private commercial banks in Iraq during the study period (2016-2021), using a Panel Data model. The study focuses on examining how operational performance and the level of risks affect the added market value of private commercial banks in Iraq. The study provides a comprehensive analysis over time and across various banks, aiding in understanding the developments and relationships throughout this time period. The results of this study can contribute to improving strategic management and decision-making within the Iraqi banking sector during this timeframe.